2012
DOI: 10.1063/1.4766282
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of plasmonically enhanced interdot energy transfer in quantum dot solids via photo-oxidation

Abstract: We studied the impact of photophysical and photochemical processes on the interdot Forster energy transfer in monodisperse CdSe/ZnS quantum dot solids. For this, we investigated emission spectra of CdSe/ZnS quantum dot solids in the vicinity of gold metallic nanoparticles coated with chromium oxide. The metallic nanoparticles were used to enhance the rate of the energy transfer between the quantum dots, while the chromium oxide coating led to significant increase of their photo-oxidation rates. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In fact, recently, we have shown Cr oxide can accelerate photo-oxidation of such QDs. 38,39 Therefore, if instead of about 1 s of irradiation, as the case of this paper, we irradiate these QDs over a much longer period of time (several minutes), their core sizes shrink rapidly and their emission undergoes significant blue shifting. 38 It has also been shown that such a photo-oxidation process can suppress plasmonic enhancement of energy transfer between QDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, recently, we have shown Cr oxide can accelerate photo-oxidation of such QDs. 38,39 Therefore, if instead of about 1 s of irradiation, as the case of this paper, we irradiate these QDs over a much longer period of time (several minutes), their core sizes shrink rapidly and their emission undergoes significant blue shifting. 38 It has also been shown that such a photo-oxidation process can suppress plasmonic enhancement of energy transfer between QDs.…”
Section: Discussionmentioning
confidence: 99%
“…38 It has also been shown that such a photo-oxidation process can suppress plasmonic enhancement of energy transfer between QDs. 39…”
Section: Discussionmentioning
confidence: 99%
“…The following equation reported by Chen may then be used to determine the change in CdSe QDs' radii due to photooxidation 16,41…”
Section: Figmentioning
confidence: 99%
“…15 We have also shown that when metallic nanoparticles are coated with an ultrathin layer of Cr oxide, the plasmonic enhancement of the energy transfer between CdSe/ZnS QDs can be suppressed with irradiation. 16 These prior results suggest that when a substrate is coated with an ultrathin layer of a specific metal oxide, it can be used as a photo-active substrate to study some of the characteristic features of QDs using the unique photocatalytic effects of the oxide. Utilizing such photo-active substrates (PASs), our objective in this paper is to investigate the impact of the structures of colloidal QDs, including their cores, shells, and ligands, on their photophysical and photochemical properties and the way such QDs interact with the environment (including the PASs) and light.…”
Section: Introductionmentioning
confidence: 99%
“…13 When MNPs are coated with a ultrathin layer of Cr oxide and irradiated, this accelerated photo-oxidation can even supress plasmonic enhancement of F€ orster resonance energy transfer (FRET) between QDs. 14 In this paper, we investigated the emission of QDs when they were deposited on plasmon-metal oxide substrates. These substrates consisted of arrays of gold (Au) nanorods (NRs) embedded in a dielectric material and coated on the top with a nanometer-thin layer of Al oxide (Fig.…”
mentioning
confidence: 99%